Narrating Nadia: An Interview Lost between Translation and a Kidnapping - Honein, Natalie (Narrative Works, 2013)
This paper is a narrative inquiry into a series of interviews conducted by the author, uncovering an aspect of her family's oral history. The interviews revolved around her grandmother's experience with her son's kidnapping and permanent disappearance in 1976, during the Lebanese civil war. From a post-modern perspective, the author assesses her place as an active participant in the conversations. Within this framework, she reflects on how language and culture came in the way of her conversations; on the power she held in translating and presenting her grandmother's words; and on translating silences and non-verbal messages.